Multi-agent based coordinated protection systems for distribution feeder fault diagnosis and reconfiguration. (April 2018) - Rahman, M.S.; Isherwood, N.; Oo, A.M.T.
Highlights: A multi-agent protection scheme is designed for fault diagnosis in distribution feeder. Agent communication and coordination provide distribution feeder reconfiguration. Agent-based protection scheme ensures to restore as many loads as possible. Proposed system provides effective backup protection through information exchange. Performance is evaluated on open ring distribution feeder under various scenarios. Abstract: This paper presents an innovative peer-to-peer agent-based protection system for fault diagnosis and automatic power restoration in power distribution networks. In practice, modern digital relays play a vital role for handling faults by allowing different switching configurations of opening and closing the circuit breakers in power networks. An effective fault detection and diagnosis along with backup protection is essential in order to save the systems from collapse and reconfigure them properly after an outage. In the proposed agent-based protection scheme, a hierarchy of two categories of agents- (i) Relay agent and (ii) Configuration agent is designed where the agent communication plays an important role to effectively diagnose the fault conditions and thereby, restore the system through proper relay coordination. An open ring feeder distribution system is considered to evaluate the performance of the proposed protection scheme. Furthermore, the impacts of both communication failure and physical protection misoperation are also addressed in this paper through effective backup protection provided by the coordination of agents.